HEAVY METALS IN STREAM SEDIMENTS AFFECTED BY A LANDFILL AND ASSOCIATED IMPACT ON GROUNDWATER QUALITY - Koutsopoulou, E.; Tsolis-Katagas, P.; Papoulis, D. (Bulletin of the Geological Society of Greece, 2010)
Sanitary landfill facilities are essential to modern societies as repositories for municipal solid wastes. However, they always entrain a certain risk of environmental impact. For this reason monitoring is essential to their operation. In the present work, the environmental impact of such a landfill is studied. Soil samples were collected in and around the landfill and their mineralogy was studied. Top layers of stream sediments were collected to examine possible dispersion of pollutants in the environment. Chemical analyses showed enrichment in As, Cu, Zn, and Pb in the stream sediments compared to uncontaminated samples. The presence of anions such as chloride, sulphate and phosphate adsorbed on clay minerals suggest the interaction of stream sediments with run-off water from the landfill. The groundwater near the landfill site was characterised as not potable and not suitable for irrigation purposes, because some parameters such as NO3 - and Cl- were close or exceeded the permissible limits given by EE, EPA and WHO.